Tradhisi Pethik Laut di Kecamatan Muncar Kabupaten Banyuwangi Kajian Folklor - Lenny Ayu Rahmawati; Octo Dendy Andriyanto (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Tradition is a form of ancestral heritage that is still preserved today. Traditions are related to beliefs that have certain goals. The author researched the sea pethik tradition held in Muncar District, Banyuwangi Regency. The Sea Picking tradition is a tradition held by the fishing community of Muncar District on the 15th of the month of Muharram or the month of Sura. The Sea Picking Tradition in Muncar District, Banyuwangi Regency has become a form of gratitude to God. God gives safety and sustenance, in the form of fish which are useful for the lives of the fishermen of the Muncar community. The aim of the author in conducting this research is several things, such as explaining the beginning, all the activities, tools and materials, the meaning of the tools and materials, the function and benefits of the Petik Laut tradition in Muncar District, Banyuwangi Regency. The author conducted this research using qualitative research. Because qualitative data is data in the form of words, schemes and images. In this research, the data method used is descriptive qualitative data. So that the data taken and processed from the data source is transformed into described qualitative data. The author uses folklore theory for research, namely folklore theory originating from Danandjaja (1984:1-2). Folklore theory is a number of cultures that are collective, spread and passed down from generation to generation, traditionally and have different versions. The data sources in this research come from interviews and observations. So as to produce research that is in accordance with the aim of carrying out research on the sea picking tradition in Muncar District, Banyuwangi Regency.